Asymmetric synthesis of spirocyclic isobenzofuranones via a squaramide-catalysed sulfa-Michael desymmetrisation reaction. Issue 12 (7th March 2023) - Tamanna,; Sharma, Deepak; Chauhan, Pankaj
Abstract : Herein, we describe the enantioselective synthesis of spirocyclohexenone isobenzofuranones through a sulfa-Michael addition/desymmetrization reaction catalyzed by a squaramide organocatalyst. Abstract : Enantioselective synthesis of spirocyclohexenone isobenzofuranones has been achieved through an organocatalysed sulfa-Michael desymmetrisation reaction. A cinchona-derived squaramide effectively promotes the desymmetrisation of spirocyclic 2, 5-cyclohexadienone isobenzofuranones via the controlled addition of various aryl thiols to generate two vicinal stereocenters with perfect diastereoselectivities and up to very good enantioselectivities.